The Effect of Conceptual Change Models on Students' Conceptual Understanding in Learning Physics - Adriana Sari, N P E; Santyasa, I W; Gunadi, I G A (Jurnal Pendidikan Fisika Indonesia, 2021)
This study aims at describing differences of students’ conceptual understanding in learning physics between students who learn with the conceptual change model (CCM) and direct learning model (DIM). This quasi-experimental research used the pretest-posttest one-way non-equivalent control group design. The study population were students of class XI. The sample was selected by random assignment technique. Data of students’ conceptual understanding was collected with a physics conceptual test. The test in the form of multiple choice with written justification consists of 20 items. Data were analyzed descriptively and ANACOVA. As a follow-up to ANACOVA, the Least Significant Difference (LSD) was used to test the comparison of the mean scores of the treatment groups. The results showed that there were differences in conceptual understanding between students’ studying with CCM and DIM. Need to make conceptual changes will occur optimally if physics learning uses CCM.